2018
DOI: 10.1080/02701367.2017.1411578
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlations With Short, Medium, and Long Cycling Time-Trial Performance

Abstract: Therefore, trained cyclists should develop maximal aerobic power irrespective of the duration of time trial, as well as enhancements in metabolic thresholds for long-duration time trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…An overview of these studies by Faude et al shows a median r = 0.84–0.92 for several different LT concepts for endurance distances (>5km), [ 9 ] comparable to our results. There are fewer studies that have compared LT concepts and their correlation with different types of cycling endurance performance, [ 16 , 20 , 26 , 35 38 ] but correlation with endurance performances (30–90 minutes) for each concept seem to vary between these studies, see Table 5 . In addition, the comparison between concepts within these studies shows varying conclusions about which is the best concept.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of these studies by Faude et al shows a median r = 0.84–0.92 for several different LT concepts for endurance distances (>5km), [ 9 ] comparable to our results. There are fewer studies that have compared LT concepts and their correlation with different types of cycling endurance performance, [ 16 , 20 , 26 , 35 38 ] but correlation with endurance performances (30–90 minutes) for each concept seem to vary between these studies, see Table 5 . In addition, the comparison between concepts within these studies shows varying conclusions about which is the best concept.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance limit when cycling at MAP has been shown to be ~4 min in well-trained cyclists [22], thus well below the duration of the cycle segment in the paratriathlon race. Nonetheless, as Borszcz et al [8] state, MAP is highly associated with cycling timetrial performance, in spite of the duration. Moreover, Balmer et al [11] have previously reported a low coefficient of variation of MAP (1.3 %), when determined using methods of the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Bold values indicate a significant correlation to bike time (p < 0.05). durations in able-bodied athletes [4][5][6][7][8][9][10][11][12]21]. It has consistently been shown that peak power output from stepwise (20-30 min) and ramp (10-12 min) tests to exhaustion relate to cycling performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory testing has traditionally been used to determine intensities to prescribe training and to detect changes in cycling performance [1][2][3]. Nowadays, research literature suggests that field testing carries a high ecological validity [4], and it is preferred by cyclists who use portable power meters on their bicycles [5].…”
Section: Introductionmentioning
confidence: 99%